PENGARUH SOLVABILITAS, EARNING PER SHARE, RENTABILITAS TERHADAP NILAI PERUSAHAAN PADA INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 - 2019 - DUMARIANI SILALAHI; BERTHA NERPY SIAHAAN (JURNAL ILMIAH KOHESI, 2022)
The company in its development always strives to maintain its business excellence to increase corporate value. The purposeof this study was to determine the effect of solvency, earning per share, profitability on firm value in basic industries andchemicals listed on the Indonesia Stock Exchange for the 2015-2019 period. The research methodology used is multiplelinear regression analysis. The results of the study prove that solvency has no significant effect on firm value in the BasicIndustry and Chemicals Listed on the Indonesia Stock Exchange for the 2015-2019 Period. Earning per share does not havea significant effect on company value in the Basic Industry and Chemicals Listed on the Indonesia Stock Exchange for the2015-2019 Period. Profitability has a positive effect on company value in the basic and chemical industries listed on theIndonesia Stock Exchange for the 2015-2019 period. Solvency, earning per share, profitability have a positive effect on firmvalue in the basic industries and chemicals listed on the Indonesia Stock Exchange for the 2015-2019 period. Testing thecoefficient of determination (R Squaer) obtained a value of 0.37, which means that the independent variable is Solvency,earnings per share, profitability can explain the variable firm value by 37% while the remaining 63% of the firm value variableis explained by other variables not used in this study such as Return on Assets, Inflation, Company Size.